(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2009)
In this article the variability of air temperature and precipitation in Ararat Valley based on the 1948–2007 observation data for Artashat meteorological station has been analyzed. The trends of seasonal and annual air temperature and precipitation have been constructed and their statistical significance has been estimated. The interannual variability of air temperature in Armenia (13 meteorological stations) has been studied and the correlation of global air temperature and air temperature over Armenia has been estimated. For a quantitative estimation of the correlation the simple linear regression between average seasonal and annual air temperatures of the stations and corresponding global temperatures has been established. The fluctuations of surface air temperature in Armenia are revealed.